"Anion clamp" allows flexible protein to impose coordination geometry on metal ions12. Issue 37 (7th May 2015) - Wang, Minji; Lai, Tsz Pui; Wang, Li; Zhang, Hongmin; Yang, Nan; Sadler, Peter J.; Sun, Hongzhe
<x xml:space="preserve">Abstract</x> X-ray crystal structures of human serum transferrin (77 kDa) with YbIII or FeIII bound to the C-lobe and malonate as the synergistic anion show that the large YbIII ion causes the expansion of the metal binding pocket while octahedral metal coordination geometry is preserved, an unusual geometry for a lanthanide ion.